2018
DOI: 10.1177/1541931218621359
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Use In-Vehicle Technologies: Consumer Preferences and Effects on Understanding

Abstract: Advanced Driver Assistance Systems (ADAS) have the potential to increase driver safety. However, driver misuse or failure to use ADAS could mitigate potential benefits. Appropriate training is one established method for encouraging proper use of technology. An online survey of 2364 respondents revealed significant differences between utilized and preferred methods for learning to use technologies. Drivers who learned through their preferred methods reported higher understanding and use of in-vehicle systems. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 11 publications
3
22
0
Order By: Relevance
“…It is unclear, though, how training could be comprehensively and accurately delivered to drivers of vehicles equipped with Level 2 systems. Drivers say that they would prefer to learn about their vehicles at dealerships, but dealership personnel frequently lack knowledge about the technologies on the vehicles they sell (Abraham, Reimer, & Mehler, 2018; Abraham et al, 2017), and this strategy would not be applicable to nondealership used vehicle sales. It is also not realistic to expect staff at rental agencies to have the necessary knowledge about all the vehicles in their fleet or to have the time to inform their customers at the time of vehicle pick up.…”
Section: Aiding Driver Understanding and Safe Use Of The Automationmentioning
confidence: 99%
“…It is unclear, though, how training could be comprehensively and accurately delivered to drivers of vehicles equipped with Level 2 systems. Drivers say that they would prefer to learn about their vehicles at dealerships, but dealership personnel frequently lack knowledge about the technologies on the vehicles they sell (Abraham, Reimer, & Mehler, 2018; Abraham et al, 2017), and this strategy would not be applicable to nondealership used vehicle sales. It is also not realistic to expect staff at rental agencies to have the necessary knowledge about all the vehicles in their fleet or to have the time to inform their customers at the time of vehicle pick up.…”
Section: Aiding Driver Understanding and Safe Use Of The Automationmentioning
confidence: 99%
“…But as drivers are using the DIT during regular driving in their own car, initial appropriate automation use is critical for traffic safety. Still, although most learning is believed to occur during the initial interaction [7,8,54], it may still be necessary to increase the duration of the DIT to obtain a higher final performance level, especially since multiple studies, like those by Beggiato [7,54] and Forster [8], have shown that the learning curve stabilizes after approximately five interactions (or 3.5 h) [7,8]. Extended DIT support may also be necessary as situations that have not been experienced for a long time can fade from the driver's mental model [7].…”
Section: Discussionmentioning
confidence: 99%
“…ACC1 was the very first scenario that all drivers encountered during the study. As discussed earlier, drivers need repeated experience and feedback to develop a calibrated level of trust [7,8,62]. While reassurance feedback may support a higher initial level of trust, a DIT should never suggest that the automation can perfectly handle a situation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations